2008
DOI: 10.1016/j.jasms.2007.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Automated in-line gel filtration for native state mass spectrometry

Abstract: Characterization of protein-ligand complexes by nondenaturing mass spectrometry provides direct evidence of drug-like molecules binding with potential therapeutic targets. Typically, protein-ligand complexes to be analyzed contain buffer salts, detergents, and other additives to enhance protein solubility, all of which make the sample unable to be analyzed directly by electrospray ionization mass spectrometry. This work describes an in-line gel-filtration method that has been automated and optimized. Automatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Sample purity and integrity were first analyzed using a self-packed buffer exchange column 50 (P6 polyacrylamide gel, BioRad, Hercules CA), coupled online to an Exactive Plus EMR Orbitrap instrument (Thermo Fisher Scientific) modified to incorporate a quadrupole mass filter and allow surface-induced dissociation. For online buffer-exchange, 200 mM ammonium acetate, pH 6.8 (AmAc) was used as a mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…Sample purity and integrity were first analyzed using a self-packed buffer exchange column 50 (P6 polyacrylamide gel, BioRad, Hercules CA), coupled online to an Exactive Plus EMR Orbitrap instrument (Thermo Fisher Scientific) modified to incorporate a quadrupole mass filter and allow surface-induced dissociation. For online buffer-exchange, 200 mM ammonium acetate, pH 6.8 (AmAc) was used as a mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…238 This method was further improved to provide robust removal of non-volatile salt in a rapid and efficient manner using self-packed gel filtration columns and automated using traditional HPLC equipment. 234,239 Additionally, online desalting methods based on diffusion, 240 dialysis, 241,242 and electrophoresis 243 have also been demonstrated.…”
Section: Emerging Complementary Technologiesmentioning
confidence: 99%
“…Building off the work by Cavanagh et al . and Waitt et al ., 234,239 we recently showed that online desalting can be implemented easily in any native MS lab for the routine screening of native protein complexes. VanAernum et al showed that a wide range of proteins and protein complexes can be separated from different biological buffers including phosphate, Tris and HEPES- based buffers, as well as different additives such as glycerol, imidazole, and DMSO.…”
Section: Emerging Complementary Technologiesmentioning
confidence: 99%
“…Online buffer exchange coupled to native mass spectrometry (OBE nMS) was first described by Cavanagh et al, 7 with further development and potential use for drug discovery being reported by Waitt et al 8 More recently OBE has been implemented as a fast desalting step after hydrophobic interaction chromatography (HIC) separation coupled online with native MS. 9 The separation of proteins from non-volatile small molecules is accomplished by a short size exclusion column, typically PEEK tubing filled with a porous stationary phase. We have improved upon and implemented OBE nMS to accommodate aqueous mobile phases containing enough ammonium acetate to provide sufficient ionic strength to maintain native protein structure and prevent interactions between analytes and the stationary phase.…”
Section: Development Of the Protocolmentioning
confidence: 99%